104 Changes in Resting Microvascular Resistance Explain Why Resting Flow is Preserved Despite Increasing Stenosis Severity: The Results of the Largest International Combined Coronary Pressure and Flow Study. (6th June 2015) - Nijjer, Sukhjinder; Waard, Guus de; Hoef, Tim van de; Sen, Sayan; Petraco, Ricardo; Echavarria-Pinto, Mauro; Lavieren, Martijn van; Danad, Ibrahim; Knaapen, Paul; Escaned, Javier; Piek, Jan; Royen, Niels Van; et al.
Abstract : Background: We sought to use combined intracoronary pressure and flow velocity measurements to elucidate of the behaviour of the human coronary circulation in response to a stenosis. Methods: 567 coronary vessels underwent simultaneous intracoronary pressure and flow velocity assessments, from which coronary flow velocity, transtenotic gradient (TG) and microvascular resistance (MVR) were computed. Measurements were made during rest over the whole cardiac cycle and the diastolic wave-free period (wfp), and also during adenosine-mediated hyperaemia. Stenoses was stratified according to severity as objectively determined by fractional flow reserve (FFR). Data is mean±SEM. Linear regression analysis estimated trends and P-values. Results: The key results are shown in the Figure 1 . As stenosis severity increases, from reference angiographically normal vessels to those with FFR≤0.50, resting flow velocity changed little (whole cycle, 18 ± 0.5 cm/s; p = 0.40, wfp, 25 ± 0.7 cm/s, p = 0.30). In contrast, hyperaemic flow falls from 45 to 19 cm/s (P < 0.01). With increasing stenosis severity, distal pressure falls such that the TG increases from 1.5 to 46 mmHg at rest (whole cycle) and 1.6 to 56 mmHg for wfp; hyperaemic TG similarly falls from 3.5 to 55 mmHg (P < 0.01 for all). Resting MVR declines as stenoses increase in severity, from 6.2 to 4.2 mmHg/cm/s at rest (P < 0.01), over the wfp from 4.4 to 2.0 mmHg/cm/s (p < 0.01); overall hyperaemic resistance was consistent across stenoses (2.3 ± 1.1 mmHg/cm/s; P = 0.19) but with a trend to suggest paradoxical vasoconstriction in severe stenoses. Conclusions: With progressive stenosis severity, distal coronary pressure falls and transtenotic gradients enlarge but resting coronary flow is preserved and maintained by a compensatory reduction of microvascular resistance. This confirms coronary auto-regulation under resting conditions in humans and explains why resting pressure gradients can detect the haemodynamic stenosis significance. Resting gradients are therefore an assessment of the natural physiological response of a given coronary bed to the presence of a stenosis. This work is also pertinent for non-invasive approaches that attempt to model physiology using anatomy since we describe all three physiological parameters across a large dataset from real-world patients. Finally, the stability of resting flow across a wide-spectrum of stenoses suggests that it should be feasible to predict the change in a resting pressure index or gradient before stenting a given stenosis.